Identifying the provisioning policies of Belgian banks - Emrah Arbak (National Bank of Belgium, 2017)
Loan loss reserves make up an essential part of a bank's soundness and more generally its viability. An under-provisioned reserve account implies that capital ratios may overstate a bank's ability to absorb future losses. For this reason, both supervisory authorities and investors regularly assess the adequacy of the loan loss provisions alongside the more popular capital ratios. The aim of the paper is to identify what motivates the loss provisioning policies employed by Belgian banks, especially whether banks use provisioning to inter-temporally smooth their earnings or capital positions. Owing to the relatively long data series, the paper also investigates whether the introduction of the IAS-39 "incurred loss" accounting standards or the onset of the financial crisis in 2008/9 had any impact on the provisioning decisions. The results show that provisioning practices of Belgian banks have been rather tightly linked to future losses, although the relationship has weakened considerably after the introduction of the IAS-39 standards and, to a lesser extent, after the financial crisis. There is also evidence that Belgian banks might have used provisioning decisions to manage their current earnings and to some extent to signal future profitability, although the latter motive also appears to have weakened after the introduction of IAS-39 standards.
Keywords: C23; G14; G21; G28; M41; 330; Belgian credit institutions; loan loss provisioning; event-based provisioning; forward-looking provisioning; earnings-smoothing; cyclical provisioning; implementation of international accounting standards